Giant Prolactinoma Causing Hydrocephalus and Intracranial Hypertension as First Manifestations of Multiple Endocrine Neoplasia Type 1 - Dantas, Naiara C. B.; Soares, Carlos E. L.; Martins, Manoel R. A.; Lourenço, Delmar M.; Quidute, Ana R. P. (Frontiers in Endocrinology, 2019)
Context: Overall, giant prolactinomas are rare tumors (4%), especially those larger than 60 mm (1%). Despite the predominance of macroadenoma documented in multiple endocrine neoplasia type 1 (MEN1)-related prolactinoma, only three giant prolactinoma cases were described so far (size > 40 mm and prolactin > 1,000 ng/mL). None of them was larger than 60 mm or presented hydrocephalus or intracranial hypertension (ICH) as initial manifestation of MEN1. Case Description: A 21-years-old man presented with ICH as the first clinical manifestation of MEN1. He harbored a MEN1 germline mutation but refused periodic vigilance after normal hormonal screening at age 14 years. During investigation, magnetic resonance imaging (MRI) of the skull showed an expansive sellar/parasellar lesion (75 × 44 × 36 mm) with moderate to severe supratentorial obstructive hydrocephalus and an extremely high serum prolactin (PRL) of 10,800 ng/mL, without combined hypersecretion of other pituitary hormones. He was diagnosed with giant prolactinoma, and cabergoline was initiated. The patient evolved with early improvement of clinical complaints for hydrocephalus and ICH and PRL reached normal values (11 ng/mL) in association with significant tumoral shrinkage after 18 months on cabergoline. After 2 months of cabergoline, cerebrospinal fluid leakage was diagnosed and corrective surgery was provided. The mean dose of cabergoline was 3 mg/week throughout treatment. Conclusion: We reported the first case with hydrocephalus and ICH as the initial clinical manifestation of a giant prolactinoma in MEN1. From our knowledge, this is the largest MEN1-related prolactinoma reported so far. Notably, all four MEN1-related giant prolactinomas cases reported were younger than 21 years strengthening the importance to routine MEN1 genetic testing for prolactinoma in this age group. Also, they all had initial effective response with dopamine agonist ensuring this drug as first-line treatment for MEN1-related giant prolactinoma. However, the scarce number of treated patients and progression of cabergoline resistance in two of them suggest strict surveillance.